MALDI-MS Imaging of Urushiols in Poison Ivy Stem - Aziz, Mina (Molecules, 2017)
Urushiols are the allergenic components of Toxicodendron radicans (poison ivy) as well as other Toxicodendron species. They are alk-(en)-yl catechol derivatives with a 15- or 17-carbon side chain having different degrees of unsaturation. Although several methods have been developed for analysis of urushiols in plant tissues, the in situ localization of the different urushiol congeners has not been reported. Here, we report on the first analysis of urushiols in poison ivy stems by matrix-assisted laser desorption/ionization-mass spectrometry imaging (MALDI-MSI). Our results show that the urushiol congeners with 15-carbon side chains are mainly localized to the resin ducts, while those with 17-carbon side chains are widely distributed in cortex and vascular tissues. The presence of these urushiols in stem extracts of poison ivy seedlings was confirmed by GC-MS. These novel findings provide new insights into the spatial tissue distribution of urushiols that might be biosynthetically or functionally relevant.